2017
DOI: 10.3390/nu9040375
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Citrulline Supplementation and Later Exposure to a High Fructose Diet in Rats Born with a Low Birth Weight: A Preliminary Report

Abstract: A low birth weight (LBW) leads to a higher risk of metabolic syndrome in adulthood. Literature suggests that citrulline supplementation in adulthood prevents the effect of a high fructose diet on energy metabolism. Whether neonatal citrulline supplementation would alter early growth or energy metabolism in the long-term in rats with LBW is unknown. LBW pups born from dams fed a low (4%) protein diet, were nursed by normally-fed dams and received isonitrogenous supplements of either l-citrulline or l-alanine by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Similarly, maternal supplementation with l -citrulline prevented hypertension and ADMA/NO imbalance in rats treated prenatally with dexamethasone [ 103 ]. Despite all these positive findings for perinatal enrichment, supplementation of rats during the pre-weaning stage was shown to predispose the animals in adulthood to lipid profiles that could potentially culminate in liver disease [ 104 ]. Thus, additional studies will be necessary to ensure the safety of l -citrulline supplementation at all stages of life.…”
Section: Anti-hypertensive Effects Of L -Citrulmentioning
confidence: 99%
“…Similarly, maternal supplementation with l -citrulline prevented hypertension and ADMA/NO imbalance in rats treated prenatally with dexamethasone [ 103 ]. Despite all these positive findings for perinatal enrichment, supplementation of rats during the pre-weaning stage was shown to predispose the animals in adulthood to lipid profiles that could potentially culminate in liver disease [ 104 ]. Thus, additional studies will be necessary to ensure the safety of l -citrulline supplementation at all stages of life.…”
Section: Anti-hypertensive Effects Of L -Citrulmentioning
confidence: 99%
“…In turn, the Thr deficiency may impair the synthesis of crucial mucosal cellular proteins and the maturation of intestine. Cit, a non-essential AA that is not incorporated into a protein, is produced in the small intestine and participate in the urea nitrogen cycle (20); It has been shown that the enterocytes are responsible of Cit synthesis (21). Intestinal epithelial injury can cause reduced Cit production as shown in necrotizing enterocolitis (NEC), short bowel syndrome and numerous other intestinal disease states (22)(23)(24)(25), which indicated that Cit levels may be correlated with functional intestinal mass potentially The lower Cit concentration during transition may suggest the intestine is relatively immature in the EUGR group compared with non-EUGR group.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have raised concerns about the effect of hyperthreoninemia on the developing brain, however, its effect on growth is blurry. Neonatal Cit administration would enhance growth and prevent the metabolic consequences of intrauterine growth retardation through an "imprinting" effect on the liver lipidome and fat metabolism (20,26). We examined contemporaneous nutrition intakes during the transitional phase and found that infants in the EUGR group had protein and energy deficits in EN during phase 1 and the early transitional phase (phase 2), compared with infants in the non-EUGR group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, maternal consumption of GSE in rats prevented a rise in TG levels in 90-and 180-day-old offspring, however, it had no significant effect on total cholesterol levels [17]. On the contrary, in a low-birth-weight and HF diet-induced model of metabolic dysfunction, a citrulline supplement given to neonates of protein-restricted dams increased liver TG content and lowered the hepatic cholesterol level, but did not alter plasma TG and HDL as well as glucose metabolism at post-natal day 90 in rats [88]. This can be explained in part by the action of citrulline in the upregulation of Fas and Srebp1, which promotes lipogenesis, as reported in this study.…”
Section: Phytochemicalsmentioning
confidence: 92%
“…Some plant extracts and phytochemicals have been shown to lower insulin resistance, thereby improving insulin action on target tissues. The resultant effect is the normalization of blood glucose levels, although some studies reported that some of these phytochemicals or plant extracts exert no significant effect on glucose levels and insulin sensitivity 72 , 88 . Two studies on GTE have given conflicting reports on the glucose profile and insulin sensitivity 16 , 69 .…”
Section: Beneficial Effects Of Phytochemicals and Plant Extracts Agai...mentioning
confidence: 99%